Analisis Pengambilan Keputusan Dalam Kendala Di UMKM Sop Iga Jeletot Terazz Karawang - Diah Nurhalizah; Jinny Wulandari; Nanda Aulia Ramadhani; Ujang Suherman (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to analyze the marketing strategy of SOP Iga Jeletot Terazz MSME in Karawang which is considered not optimal in increasing competitiveness and expanding the market. The research method used is qualitative with an explanatory survey approach, collecting data through in-depth interviews with MSME owners and employees. The results of the study indicate that the marketing strategy of this MSME is still conventional, does not utilize social media in a structured manner, and has not implemented data-based marketing. The main influencing factors are limited human resources, lack of understanding of digital marketing, and the absence of a customer loyalty program. In the discussion, this problem is associated with decision-making theory, including the stages of problem analysis, alternative selection, and implementation and evaluation of decisions. More effective marketing strategies include planning social media content, using digital advertising, and implementing loyalty programs. In addition, training human resources to improve digital marketing competency is an important step. This study concludes that with the adoption of technology-based marketing strategies and careful planning, SOP Iga Jeletot Terazz MSME has the opportunity to increase competitiveness and expand market reach.